Macroalgal Defenses Against Herbivory: Causes and Consequences of Intraspecific Variation - Haavisto, Fiia (fi=Turun yliopisto|en=University of Turku|, 2016)
In marine benthic communities, herbivores consume a considerable proportion of primary producer biomass and, thus, generate selection for the evolution of resistance traits. According to the theory of plant defenses, resistance traits are costly to produce and, consequently, inducible resistance traits are adaptive in conditions of variable herbivory, while in conditions of constant/strong herbivory constitutive resistance traits are selected for. The evolution of resistance plasticity may be constrained by the costs of resistance or lack of genetic variation in resistance. Furthermore, resource allocation to induced resistance may be affected by higher trophic levels preying on herbivores. I studied the resistance to herbivory of a foundation species, the brown alga Fucus vesiculosus. By using factorial field experiments, I explored the effects of herbivores and fish predators on growth and resistance of the alga in two seasons. I explored genetic variation in and allocation costs of resistance traits as well as their chemical basis and their effects on herbivore performance. Using a field experiment I tested if induced resistance spreads via water-borne cues from one individual to another in relevant ecological conditions. I found that in the northern Baltic Sea F. vesiculosus communities, strength of three trophic interactions strongly vary among seasons. The highly synchronized summer reproduction of herbivores promoted their escape from the top-down control of fish predators in autumn. This resulted into large grazing losses in algal stands. In spring, herbivore densities were low and regulated by fish, which, thus,enhanced algal growth. The resistance of algae to herbivory increased with an increase in constitutive phlorotannin content. Furthermore, individuals adopted induced resistance when grazed and when exposed to water-borne cues originating from grazing of conspecific algae both in the laboratory and in field conditions. Induced resistance was adopted to a lesser extent in the presence of fish predators. The results in this thesis indicate that inducible resistance in F. vesiculosus is an adaptation to varying herbivory in the northern Baltic Sea. The costs of resistance and strong seasonality of herbivory have likely contributed to the evolution of this defense strategy. My findings also show that fish predators have positive cascading effects on F. vesiculosus which arise via reduced herbivory but possibly also through reduced resource allocation to resistance. I further found evidence that the spread of resistance via water-borne cues also occurs in ecologically realistic conditions in natural marine sublittoral. Thus, water-borne induction may enable macroalgae to cope with the strong grazing pressure characteristic of marine benthic communities. The results presented here show that seasonality can have pronounced effects on the biotic interactions in marine benthic communities and thereafter influence the evolution of resistance traits in primary producers.

Merenpohjan eliöyhteisöissä kasvinsyöjät kuluttavat suuren osan perustuottajien biomassasta ja voimakkaan kasvinsyönnin tuottama luonnonvalinta onkin johtanut perustuottajien resistenssipiirteiden evoluutioon. Silloin kun kasvinsyönnin voimakkuus vaihtelee ajallisesti ja paikallisesti ja kun resistenssistä on kustannuksia, kasvin oletetaan puolustautuvan indusoituvan resistenssin avulla. Jatkuvan tai voimakkaan kasvinsyönnin puolestaan oletetaan johtavan konstitutiivisen resistenssin evoluutioon. Resistenssin evoluutiota voivat rajoittaa resistenssin kustannukset tai geneettisen muuntelun puute. Resistenssipiirteiden ilmenemiseen voivat vaikuttaa myös kasvinsyöjiä saalistavat pedot. Väitöskirjassani tutkin resistenssipiirteiden evoluutiota monivuotisella ruskoleviin kuuluvalla Fucus vesiculosus rakkolevällä. Luonnossa tehdyillä kokeilla tutkin kasvinsyöjien ja kasvinsyöjiä saalistavien kalojen vaikutusta rakkolevän kasvuun ja resistenssiin eri vuodenaikoina. Tutkin myös resistenssipiirteiden muuntelun määrää ja allokaatiokustannuksia sekä resistenssin kemiallista perustaa ja sen vaikutusta kasvinsyöjien kasvuun ja lisääntymiseen. Testasin luonnonolosuhteissa, leviääkö rakkolevän resistenssi vesivälitteisten yhdisteiden avulla yksilöstä toiseen. Havaitsin, että vuodenaikaisuus pohjoisella Itämerellä vaikuttaa lajien välisten vuorovaikutusten voimakkuuteen. Kasvinsyöjien yhtäaikainen lisääntyminen kesällä näkyi syksyllä niiden suurina tiheyksinä ja rakkolevän suurena kulutuksena. Keväällä kasvinsyöjätiheydet olivat pieniä. Kalat eivät vaikuttaneet kasvinsyöjätiheyksiin syksyllä, mutta niiden saalistus vähensi kasvinsyöjiä keväällä, mikä paransi rakkolevän kasvua. Rakkolevä puolustautui kasvinsyöjiä vastaan. Korkea konstitutiivinen fenolisten yhdisteiden, florotanniinien, määrä lisäsi levien resistenssiä. Sekä kasvinsyöjien syönti että syödystä naapurilevästä peräisin olevat vesivälitteiset yhdisteet indusoivat rakkolevän resistenssin niin laboratorio- kuin luonnonolosuhteissa. Resistenssin indusoituminen oli heikompaa kalojen läsnä ollessa. Tulokseni viittaavat siihen, että rakkolevän indusoituva resistenssi on sopeuma pohjoisen Itämeren vaihtelevaan kasvinsyöntiin. Resistenssin kustannukset ja kasvinsyönnin vuodenaikaisuus ovat todennäköisesti suosineet resistenssin plastisuuden evoluutiota. Kalat vaikuttavat positiivisesti rakkolevään paitsi vähentämällä kasvinsyöntiä mahdollisesti myös vähentämällä resurssien allokointia resistenssiin. Vesivälitteinen makrolevien resistenssin leviäminen todennäköisesti edesauttaa niitä selviämään merenpohjan levä- yhteisöille tunnusomaisesta voimakkaasta kasvinsyönnistä. Väitöskirjani tulokset osoittavat, että lajien välisillä vuorovaikutussuhteilla ja niiden vuodenaikaisella vaihtelulla on keskeinen merkitys merenpohjan eliöyhteisöjä muokkaavana tekijänä.